Antiproliferative and antioxidant activity of nitrato-[4-(3,4-dimethylphenyl)-2-(2-oxo-3-methoxybenzylidene) hydrazinecarbothioamido]copperInternational [Articol] - Gulea, A.P.; Gudumac, V.S.; Garbuz, O.S.; Cebotari, D.Y.; Spinu, I.C.; Pirvu, O.I.; Sardari, V.V.; Tagadiuc, O.C.; Gostev, I.V.; Spinu, C.I.; Scoferta, P.G. (Marina Sokolova Publishings, 2018)
In the present study, the ability of nitrato-[4-(3,4-dimethylphenyl)-2-(2-oxo-3-methoxybenzylidene) hydrazinecarbothioamido] copper (CDI-14) – new coordination compound of the thiosemicarbazone class of biometals to induce the inhibition of proliferation in HeLa and BxPC-3 cancer cell lines was investigated. Its cytotoxicity against MDCK normal cell line was also evaluated. The viability of each cell line was determined by the Resazurin test. Doxorubicin was used as a positive control. The antioxidant activity was evaluated by ABTS assay and compared with those of the standards, trolox and rutin.Obtained results showed that compound CDI-14 has a good antioxidant potential and high antiproliferative activity against HeLa and BxPC-3 cancer cell lines. It was also observed that the tested compound did not affect the cytotoxic activity of MDCK normal cell line, which indicates its selective toxicity and the possibility of its use as an anticancer agent.
АНТИПРОЛИФЕРАТИВНАЯ И АНТИОКСИДАНТНАЯ АКТИВНОСТИ НИТРАТО-[4-(3,4-ДИМЕТИЛФЕНИЛ)-2-(2-ОКСО-3-МЕТОКСИБЕНЗИЛИДЕН) ГИДРАЗИНКАРБОТИОАМИДО] МЕДИ
Keywords: antiproliferative activity; antioxidant activity; selective activity; антипролиферативная активность; антиоксидантная активность; избирательная активность